Pemilihan Padi Terbaik Pada Kelompok Tani Sri Rejeki dengan Metode WP (Weighted Product) - Angga Yogi Pratama; Edo Tio Gunawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
At this time the best rice was very diverse. This makes fertile beautiful village farmers having difficulty choosing the best type of rice that will be made of quality rice. Until recently, this was done in the traditional way, such as waiting for the harvest to find out. So that we need a decision support system used in selecting the best rice type. In this decision making system will use the Weighted Product method to determine alternatives and criteria. The criteria that will be used to determine the best rice are price, quality, harvest time, popularity, maintenance costs and durability. The alternatives that are chosen are Rice Hebrides, Padi Impara, Padi Impari and Padi 64. In testing and implementation, the best rice yields can be obtained with several alternatives, namely hybrid rice which is the first alternative which is made as quality rice